Adesão de enfermeiros de um hospital a um protocolo de prevenção de quedas : estudo quase-experimental - Cunha, Carla Rafaela Teixeira (2020)
ABSTRACT: To assess nurses' adherence to a fall prevention protocol at a university hospital submitted to an intervention focused on self-efficacy. Method: Quasi-experimental study done with 23 nurses from a university hospital in the city of Cuiabá-Mato Grosso. Nurses who developed care activities in the adult, child and adolescent inpatient, pre-delivery / childbirth / postpartum and intensive care units for adults and were included in the effective staff of these units by the end of the study were included. They participated in an intervention based on self-efficacy and were evaluated before and after the intervention. Demographic and professional data were collected through a questionnaire (pre-intervention), self-efficacy (pre and post-intervention) using the General and Perceived Self-Efficacy Scale. The measure of nurses' adherence (pre and post-intervention) to the fall prevention protocol was carried out by verifying the number of records of assessment of the risk of falling carried out in the medical records by nurses within 24 hours after patients' admission. Analysis: Performed in the SPSS 14.0 program using the paired t-test, Fisher's exact test (qualitative independent variables) and the Mann-Whitney test (quantitative independent variables). The level of significance was set at p <0,05. Research approved by the Research Ethics Committee of the Hospital Universitário Júlio Muller with the opinion number 3.181.194. Results: Presented in the form of two manuscripts. The first analyzed the association between nurses' adherence to a fall prevention protocol with demographic, professional and self-efficacy variables. As a result, 39,13% of nurses (95% CI: 20,62; 61,39) adhered to the protocol and there was a significant difference in adherence between clinics (p = 0,006), of which the greatest adherence was in medical, surgical clinics and pediatric. The second analyzed nurses' adherence to a fall prevention protocol in a hospital before and after an intervention based on self-efficacy. When comparing the averages of adherence rates (pre and post-intervention), there was an increase from 11,07% in the pre-intervention to 32,87% in the post-intervention. This difference was statistically significant (p = 0,015). Regarding self-efficacy, the post-intervention averages (40,91) slightly increased compared to the pre-intervention (40,52) and the difference was not statistically significant (p = 0.70). Conclusion: The average total nurses' adherence to the fall prevention protocol increased significantly after the intervention based on self-efficacy. It is believed that this result was related more to the strategies used in the intervention, than to self-efficacy. The association between nurses' adherence to a fall prevention protocol and the units in which they work was also evidenced. The characteristics of patients admitted to these units may have influenced adherence.